2002
DOI: 10.1034/j.1600-0897.2002.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with Dendritic Cells (DCs) control fetal abortion rate in the CBA/J × DBA/2J mouse model

Abstract: DBA/2J mated‐CBA/J female mice are prone to a high incidence of fetal abortions. This fetal wastage can be dramatically reduced by immunizing the female mice with BALB/c, but not DBA/2J spleen cells during early gestation, whereas underlying mechanisms remain to be elucidated. Recently, DCs have been described at the feto‐maternal interface in human uterus. The aim of this study was to analyse the role of DCs in the maintenance of pregnancy in the CBA/J × DBA/2J model. Bone marrow derived DCs were generated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, pregnancy has been labeled a ‘Th2 phenomenon’. Blois et al showed that Th1 cytokines led to pregnancy loss in mice 6 , and Chaouat et al demonstrated that this loss could be prevented by Th2 cytokines 7 . Inflammatory processes alter the balance of Th1 and Th2 cytokines and lead to a shift toward Th1 predominance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, pregnancy has been labeled a ‘Th2 phenomenon’. Blois et al showed that Th1 cytokines led to pregnancy loss in mice 6 , and Chaouat et al demonstrated that this loss could be prevented by Th2 cytokines 7 . Inflammatory processes alter the balance of Th1 and Th2 cytokines and lead to a shift toward Th1 predominance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, pregnancy has been labeled a 'Th2 phenomenon'. Blois et al showed that Th1 cytokines led to pregnancy loss in mice [6], and Chaouat et al demonstrated that this loss can be prevented by Th2 cytokines [7]. Inflammatory processes alter the balance of Th1 and Th2 cytokines and lead to a shift toward Th1 predominance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, pregnancy has been labeled a 'Th2 phenomenon'. Blois et al showed that Th1 cytokines led to pregnancy loss in mice [6], and Chaouat et al demonstrated that this loss can be prevented by Th2 cytokines [7]. In ammatory processes alter the balance of Th1 and Th2 cytokines and lead to a shift toward Th1 predominance.…”
Section: Introductionmentioning
confidence: 99%